Pengaruh Musim Terhadap Hasil Tangkapan Gurita di Pulau Langkai dan Lanjukang: The Influence of Seasons on Octopus Catches on Langkai and Lanjukang Islands - Nasdwiana; Hasmawati; Husniati (Jurnal Galung Tropika, 2024)
The existence of great potential is not supported by data and information regarding octopus catches and management. Catches in public waters are dynamic because they are influenced by various factors, especially season and rainfall. This research aims to determine the octopus catches on Langkai and Lanjukang Islands and how the season influences the octopus catches. The method used is the direct survey method, through interviews and distributing questionnaires to fishermen and collectors, with sample determination using the purposeful sampling method. Meanwhile, rainfall data was obtained from the Makassar City BMKG station. Catch data were analyzed using the SPSS t-test, while correlation analysis was used to determine the relationship between rainfall and catch. The research results show that the production of octopus catches on Langkai and Lanjukang Islands during the year, from October 2021 to September 2022, fluctuates. For catches based on season, in the rainy season, it is 8,428 kg, while in the dry season, it is 4,271 kg. The results of the analysis showed that there was a significant difference in octopus catch production in the rainy season and the dry season (p = 0.01). The correlation analysis of rainfall and catch results shows a reasonably strong correlation (0.55).